A tandem duplication within the fibrillin 1 gene is associated with the mouse tight skin mutation. - Siracusa, L D; McGrath, R; Ma, Q; Moskow, J J; Manne, J; Christner, P J; Buchberg, A M; Jimenez, S A (Genome Research, 1996)
Mice carrying the Tight skin (Tsk) mutation have thickened skin and visceral fibrosis resulting from an accumulation of extracellular matrix molecules. These and other connective tissue abnormalities have made Tskl + mice models for scleroderma, hereditary emphysema, and myocardial hypertrophy. Previously we localized Tsk to mouse chromosome 2 in a region syntenic with human chromosome 15. The microfibrillar glycoprotein gene, fibrillin 1 (FBN1), on human chromosome 15q, provided a candidate for the Tsk mutation. We now demonstrate that the Tsk chromosome harbors a 30- to 40-kb genomic duplication within the Fbn1 gene that results in a larger than normal in-frame Fbn1 transcript. These findings provide hypotheses to explain some of the phenotypic characteristics of Tskl + mice and the lethality of Tsk/Tsk embryos.